Macrobenthic Community Structure in the Northwestern Arabian Gulf, Twelve Years after the 1991 Oil Spill - Joydas, Thadickal V.; Qurban, Mohammad A.; Borja, Angel; Krishnakumar, Periyadan K.; Al-Suwailem, Abdulaziz (Frontiers in Marine Science, 2017)
The biota in the Arabian Gulf faces stress both from natural (i.e., hyper salinity and high sea surface temperature), and human (i.e., from oil-related activities) sources. The western Arabian Gulf was also impacted by world’s largest oil spill (1991 Oil Spill). However, benthic research in this region is scarce and most of the studies have been conducted only in small areas. Here, we present data on macrobenthos collected during 2002-2003 from the open waters and inner bays in the northwestern Arabian Gulf aimed to assess the ecological status and also to evaluate the long-term impact, if any, of the 1991 Oil Spill. A total of 392 macrobenthic taxa with an average (±SE) species richness (S) of 71±2, Shannon-Wiener species diversity (H') of 4.9±0.1, and density of 3,181±359 ind. m-2 was recorded from the open water stations. The open waters have “slightly disturbed” (according to AZTI’s Marine Biotic Index (AMBI)) conditions, with “good-high” (according to multivariate-AMBI (M-AMBI)) ecological status indicating the absence of long-term impacts of the oil spill. Overall, 162 taxa were recorded from inner bays with average (±SE) values of S 41±9, H' 3.48±0.39, and density 4,203±1,042 ind. m-2. The lower TPH (Total Petroleum Hydrocarbons) stations (LTS, TPH concentrations <70 mg kg-2) show relatively higher S, H' and density compared to the higher TPH stations (HTS, TPH concentrations ≥100 mg kg-2). In the inner bays, AMBI values indicate slightly disturbed conditions at all stations except one, which is moderately disturbed. M-AMBI values indicate good status at LTS, while, high, good, moderate, and poor status at HTS. The “moderately disturbed” conditions with “moderate-poor” ecological status in some locations of the inner bays specify a severe long-term impact of the oil spill.